Terminally truncated isopenicillin N synthase generates a dithioester product: evidence for a thioaldehyde intermediate during catalysis and a new mode of reaction for non-heme iron oxidases - McNeill, LA; Brown, TJN; Sami, M; Clifton, IJ; Burzlaff, NI; Claridge, TDW; Adlington, RM; Baldwin, JE; Rutledge, PJ; Schofield, CJ (Wiley, 2017)
Isopenicillin N synthase (IPNS) catalyses the oxidation of a tripeptide, L-δ-(α-aminoadipoyl)-L-cysteinyl-D-valine (ACV), to isopenicillin N (IPN), the first-formed β-lactam in penicillin biosynthesis. IPNS catalysis is dependent upon an iron(II) cofactor and oxygen as co-substrate. In the absence of substrate, the carbonyl oxygen of the side-chain amide of the penultimate residue, Gln330, co-ordinates to the active site metal. Substrate binding ablates this interaction, triggering rearrangement of seven C-terminal residues which move to take up a conformation that extends the final α-helix and encloses the active site. We report mutagenesis studies probing the role of the C-terminal and other aspects of the substrate binding pocket in IPNS. Unexpectedly, deletion of seven C-terminal residues exposes the active site and leads to formation of a new type of thiol oxidation product. The isolated product is shown by LC-MS and NMR analyses to be the ene-thiol tautomer of a dithioester, made up from two molecules of ACV linked between the thiol sulfur of one tripeptide and the oxidised cysteinyl β-carbon of the other. A mechanism for its formation is proposed, supported by X-ray crystal data which shows the substrate ACV bound at the active site, its cysteinyl β-carbon exposed to attack by a second molecule of substrate, adjacent. Formation of this product constitutes a new mode of reaction for IPNS and non-heme iron oxidases in general.